Dynamics and Factors of ESG Adoption in the Czech Republic - Balogh, Ivan (2026)
Businesses in the Czech Republic are increasingly exposed to regulatory, market, and stakeholder pressures to improve corporate environmental performance, strengthen ESG transparency, and communicate sustainability-related information credibly. This dissertation examines the organizational and contextual mechanisms through which firms respond to these pressures, with a particular focus on absorptive capability, environmental strategy, corporate environmental management performance, ESG disclosure intensity, firm-level factors, and the perceived importance of environmental claims in purchasing decisions. The dissertation consists of three empirical papers. The first paper employs covariance-based structural equation modelling (CB-SEM) to analyse internal ESG adoption based on questionnaires collected from senior managers of large Czech companies. The second paper complements this perspective by examining firm-level determinants of ESG disclosure intensity using censored regression models. The third paper applies generalized ordinal logistic regression to investigate how consumers’ individual predispositions relate to the perceived importance of environmental claims for product and service purchases. Taken together, the three papers provide a multi-level perspective on ESG adoption in the Czech context. The findings indicate that absorptive capability is positively associated with environmental strategy and indirectly associated with corporate environmental management performance through environmental strategy. In addition, firm-level characteristics, particularly company size measured by revenue and number of employees, as well as industry ESG sensitivity and profitability, are associated with higher observed ESG disclosure intensity.